Prototype Traffic Light Design Based Wireless Sensor Network With Multihop Topology - arafa laili utami (Politeknik Negeri Semarang, 2017)
Increasing number of vehicles there are not combining by the increase highway facilities and means of adequate traffic, creating traffic jams can not be avoided. Therefore, it needs a traffic light system which can change the duration adaptive, so delays in traffic flow can be parsed automatically. In this thesis constructed an traffic light prototype that can change the duration of the traffic lights adaptively according to the conditions of real-time flow of the street using a detector such as a HMC5883L compass sensor. With a wireless sensor network and multihop topologies in terms of the system is easy to apply, because it does not require the transmission line in the form of cables and sensors can be added the number and spacing range. The main components used are Arduino Uno, Arduino Mega, XBee and HMC5883L compass sensors. Compass sensor detects the presence of vehicles by calculating magnitude value in the form of interference with Earth's magnetic field caused by cars metal, so the sensor nodes can send information pathways state conditions in the one intersection to the coordinator via another sensor nodes using xbee in multihop topologies. The results obtained after testing is setting plan to address the inequality of delay on the traffic system can work well with the sensor reading error 0.09% within a period of 2 minutes and the application topology multihop use the traffic light system can expand the detection range 400 m. But the number of hops is used affects the packet loss is greater, namely 0.192% at a distance of 200 m.